The Phenomenon of 'Marriage Is Scary' and the Role of Premarital Guidance in Preparing the Mental and Emotional Health of Prospective Brides and Grooms - Mohammad Zecky Najmudin; Ishaq Ishaq; Moh. Lutfi Nurcahyono (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Contemporary societies are experiencing a growing phenomenon termed “marriage is scary,” reflecting increasing fear and anxiety toward marriage, particularly among Generation Z, amid rapid social, cultural, and economic change. Specific Background: In Indonesia, declining marriage rates and pervasive negative narratives from social media, past familial trauma, and economic uncertainty have reshaped perceptions of marriage from a sacred commitment into a source of psychological burden. Knowledge Gap: Despite mandatory premarital counseling policies, limited empirical analysis has examined whether existing counseling models adequately address the deep mental and emotional anxieties underlying this phenomenon. Aims: This study aims to analyze the roots of the “marriage is scary” phenomenon and evaluate the role of premarital guidance in strengthening the mental and emotional readiness of prospective brides and grooms. Results: Findings indicate that fear of marriage is multidimensional—spiritual, psychosocial, and economic—and that premarital counseling positively enhances emotional maturity, communication skills, and confidence, though its short duration constrains impact. Novelty: The study integrates fiqh perspectives with psychosocial theory to conceptualize marriage anxiety as both a spiritual and psychological issue. Implications: Strengthening premarital counseling through comprehensive, context-sensitive, and psychosocially informed approaches is essential for fostering resilient families and mitigating marriage-related anxiety. Highlights: Psychosocial Roots of Marriage Fear: The “marriage is scary” phenomenon emerges from social media narratives, past trauma, economic uncertainty, and weakened spiritual orientation. Strategic Role of Premarital Counseling: Premarital guidance contributes to improving emotional maturity, communication skills, and psychological preparedness of prospective couples. Need for Program Enhancement: Counseling effectiveness requires longer duration, contextual materials, and integrated psychosocial–spiritual approaches to address deep-seated anxieties. Keywords: Marriage Anxiety, Premarital Counseling, Mental Readiness, Generation Z, Family Resilience